Primary School Teachers as Reading Role Models: An Analysis of a Focus Group - Mithans, Monika; Voršič, Ines (Bralni vzori 2, 2025)
The articel presents the results of a focus group of primary school teachers, conducted in April 2025 as part of the project Reading Role Models: Reading Habits of Professional Staff in Kindergartens, Schools, Faculties and Public Libraries. The participating teachers, who teach various subjects at primary schools across different regions, responded to four questions: (1) what they consider most important in promoting the development of reading literacy; (2) which positive experiences from their practice they would recommend to others; (3) what institutions should do to raise awareness among professional staff about the importance of reading literacy and to inform educational professionals about quality reading materials; and (4) what should be done at the school level to ensure these recommendations are taken into account. Teachers unanimously affirmed the importance of developing reading literacy and emphasized mutual connection and collaboration as key to successfully achieving higher goals and levels of reading literacy.